1996
DOI: 10.22358/jafs/69597/1996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding cholesterol-enriched diet on plasma and tissue cholesterol and atherosclerosis in rabbits

Abstract: The aim of the experiment was to investigate the relationship between consumption of cholesterolenriched diet and plasma and tissue cholesterol content as well as the degree of atherosclerosis in rabbits, to make further investigations on the role of emotional and behavioural factors in diet induced atherosclerosis more conclusive. The experimental rabbits (E) were offered 150 g standard pellet feed daily mixed with 1 egg yolk and 1.5 g cholesterol in substantia during 7 weeks, whereas the control rabbits (C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The main results in this section can be summarized as follows: (1) The concentration of saturated FA in the aggregates with size < 200 nm decreases significantly with the increase of Ca 2+ and reaches a limiting value of around 0.5-1 mM at C Ca ≥ 6 mM for all studied fats; (2) The concentration of unsaturated FA in these aggregates also decreases with the increase of Ca 2+ , but does not reach a limiting value up to 11 mM Ca 2+ ; (3) The decrease in FA solubilization is due do the formation of insoluble calcium-FA soaps; (4) The saturated FA are precipitated preferentially by calcium, as compared to unsaturated FA.…”
Section: (A) Compositions Of the Serum And The Permeatementioning
confidence: 89%
See 2 more Smart Citations
“…The main results in this section can be summarized as follows: (1) The concentration of saturated FA in the aggregates with size < 200 nm decreases significantly with the increase of Ca 2+ and reaches a limiting value of around 0.5-1 mM at C Ca ≥ 6 mM for all studied fats; (2) The concentration of unsaturated FA in these aggregates also decreases with the increase of Ca 2+ , but does not reach a limiting value up to 11 mM Ca 2+ ; (3) The decrease in FA solubilization is due do the formation of insoluble calcium-FA soaps; (4) The saturated FA are precipitated preferentially by calcium, as compared to unsaturated FA.…”
Section: (A) Compositions Of the Serum And The Permeatementioning
confidence: 89%
“…[2][3][4][5] show that, by definition, α = β + γ + δ. [2][3][4][5] show that, by definition, α = β + γ + δ.…”
Section: Degree Of Tg Lipolysis Tg Transformation To Dg and Mg Occurmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore in the next experiment we applied cholesterol-enriched diet where the main source of cholesterol was pulverized cholesterol in substantia. This type of diet has increased five -fold the plasma cholesterol and three -fold the liver cholesterol level and induced the marked atherosclerosis as well as has reduced the activity of some glycolytic enzymes (KONECKA et al, 1996;KONECKA and JEZIERSKI, 1997). In the present studies we have applied the latter type of diet to study the effect on lysosomal enzymes in the liver and blood plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Schlűsselwőrter: Lysosomale Enzyme, Cholesterin, Kaninchen Cholesterol-enriched diets increase cholesterol level in body tissues, first of all in the liver (JONNALAGADA et al, 1993;KONECKA et al, 1996) and may cause pathological changes in the liver structure. Cholesterol-fed animals display fibrosis and strongly enlarged gray-white coloured liver (BEYNEN et al, 1986;KONECKA and JEZIERSKI, 1997;SIMONSEN et al, 1995) have found that prolonged intake of large amounts of dietary cholesterol had a significant effect on metabolic processes in the liver of rabbits.…”
Section: Zusammenfassung Titel Der Arbeit: Einfluss Der Mit Cholestermentioning
confidence: 99%